Design of a 2-Bit wide-angle coding metasurface for bistatic RCS reduction - Huang, Yi Fei; Jiang, Zhongjin; Liu, Lu; Zhang, Hao Chi (Frontiers in Materials, 2022)
A 2-bit wide-angle coding metasurface is proposed to decrease the bistatic radar cross section (RCS) in this study. Each meta-atom of the designed coding metasurface is composed of a wide-beamwidth microstrip antenna whose feeding port is loaded with an open stub. There are globally four phase-coding states, namely, “00,” “01,” “10,” and “11,” which are achieved in a wide-angle range through an elaborate design of the lengths of the open stubs. Simulation results indicate that, for each meta-atom, the reflective amplitude is above −1 dB, and the reflective phase difference between two adjacent coding states is limited in the range of 90° ± 25° at 8 GHz at incident angles, 0°, 20°, 40°, and 60°. In addition, the generalized Rudin–Shapiro (RS) polynomial is applied to design the coding sequence of the metasurface array to reduce bistatic RCS. A 16 × 16 metasurface array is simulated, manufactured, and measured to validate the bistatic RCS reduction. The simulated results perfectly agree with the experimental results when the incidence angle of the 8 GHz plane wave is within 60°, which shows that the coding metasurface is practical and valid.